Radial growth of slanting-columnar nanocrystalline Si on Si nanowires - Chong, S.K.; Goh, B.T.; Aspanut, Z.; Muhamad, M.R.; Dee, C.F.; Rahman, S.A. (2011)
The synthesis of Si nanowires was achieved via hot-wire chemical vapor deposition using an indium catalyst. In addition to the axial catalytic growth of Si nanowires, the radial growth of columnar structures occurred on the walls of the nanowires. The HRTEM results revealed that a mixture of amorphous Si and nanocrystalline Si grains was present within the columnar structure. The nanocrystalline Si nanocolumns were slanted at an angle of similar to 66 degrees towards the wall of the NWs. The amorphous Si background in the XRD pattern and asymmetric broadening in the Si peak of the Raman spectra provided evidence for the formation of nanocrystalline Si. (C) 2011 Elsevier B.V. All rights reserved.